Politics and Political Culture in the Court Masque - Knowles, J. author. aut Link
VIII, 288 p.
Keywords: Politics and Political Culture in the Court Masque considers the interconnections of the masque and political culture. It examines how masques responded to political forces and voices beyond the court, and how masques explored the limits of political speech in the Jacobean and Caroline periods.